The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2967/jnumed.109.067371
|View full text |Cite
|
Sign up to set email alerts
|

Chest CT and Whole-Body18F-FDG PET Are Cost-Effective in Screening for Distant Metastases in Head and Neck Cancer Patients

Abstract: The aim of the study was to define the cost-effectiveness of whole-body 18 F-FDG PET, as compared with chest CT, in screening for distant metastases in patients with head and neck squamous cell carcinoma (HNSCC). Methods: In a multicenter prospective study, 145 consecutive patients with high risk factors for distant metastases and scheduled for extensive treatment underwent chest CT and whole-body 18 F-FDG PET for screening of distant metastases. The cost data of 80 patients in whom distant metastases develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 17 publications
3
34
0
Order By: Relevance
“…Time-of-flight technology puts additional requirements on the performance of scintillating materials. Thus, LaBr, LYSO and LSO [33] are the materials currently considered for a time-of-flight PET systems. Considering that modern machines provide higher sensitivity and spatial resolution, we may have underestimated the real impact of PET/CT in our population.…”
Section: Limitations and Considerationsmentioning
confidence: 99%
“…Time-of-flight technology puts additional requirements on the performance of scintillating materials. Thus, LaBr, LYSO and LSO [33] are the materials currently considered for a time-of-flight PET systems. Considering that modern machines provide higher sensitivity and spatial resolution, we may have underestimated the real impact of PET/CT in our population.…”
Section: Limitations and Considerationsmentioning
confidence: 99%
“…Thirty-three articles were selected and retrieved in fulltext version (Figure 1). One study was found screening the references [6] and 18 articles were subsequently excluded [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . Finally, 16 studies were included [6,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the indication for metabolic imaging should be handled reluctantly. A recent study showed 18 F-FDG PET/CT is the most eVective pretreatment screening method for distant metastases in HNSCC patients with risk factors [19]. It is our opinion, that in future, when integrated 18 F-FDG PET/CT and MRI scanners become routine, this will be the most cost-eVective imaging method for SNMM.…”
Section: Limitations Of 18 F-fdg-pet/ctmentioning
confidence: 99%